Rectal ischemia causes mass formation, masquerading as rectal cancer. Issue 9 (25th August 2018) - Fousekis, Fotios; Aggeli, Panagiota; Gkogkos, Spyridon; Christou, Panagiota; Pappas-Gogos, George
Abstract: Rectal ischemia rarely occurs because of the rich vascular supply of the rectum, while endoscopic presentation of ischemic colitis always is not distinct and can uncommonly mimic malignant neoplasm. We present a case of a rectal ischemia, which presented with haematochezia and proctoscopy revealed a large ulcerating mass, masquerading as rectal cancer and obstructed the lumen of rectum. However, histological examinations showed only features for ischemic colitis and no evidence for malignancy. The patient was treated conservatively and 10 days later, new endoscopy showed complete disappearance of ulcerated mass, and new biopsies confirmed the initial diagnosis. Awareness and early diagnosis of 'mass forming' entity of ischemic colitis is very essential in order to carry out appropriate treatment and avoid severe complications.